The knowledge competency of civil engineers in construction industry - J., Izwan; I., Md Sayuti; Noram Irwan, Ramli (IOP Publishing, 2019)
Construction management’s knowledge is basis knowledge for one who works as civil engineer in construction industry. A good construction management will make the progressing of the project is more efficient and follow as in the plan also fulfill the customer needed as in the contract. The weak management will cause problem at site such as the delay, over budgeting and so on. As a civil engineer that involve direct with the site activities, they need to master this knowledge to manage the project. The purposes for this research are to identify and to determine the knowledge that a civil engineer in construction industry should have to be a competent engineer. The data collections are taken from the respondents who work as civil engineer with contractor class G6 and G7 in Penang state. The importance of this research is to determine the best knowledge characteristics that will be used for nowadays civil engineer. They will apply this knowledge during manage any project. The result from the survey will be compared with the data that get from the literature review. This is to identify the latest knowledge to be a guideline to become a competent engineer. From the result of the survey, mostly respondents who are civil engineers that involve in construction activities in Penang agree that have the knowledgeable in technical knowledge, decision making knowledge, teamwork knowledge planning and scheduling knowledge also leadership knowledge is very important to be a competent engineer.